The house of mirth. - Wharton, Edith, 1862-1937 (Open Road Integrated Media, 2016)
The classic tale of a young woman's struggle for love and money from the Pulitzer Prize-winning author of Ethan Frome and The Age of Innocence. Raised among New York's high society, Lily Bart is beautiful, charming, and entirely without means. Determined to maintain the extravagant lifestyle to which she is accustomed, Lily embarks on a mission to marry a wealthy man who can secure her station. However, the businesslike proposals from her many suitors remain fruitless, and her thoughts keep returning to the one man she truly loves. Bedeviled by debt, betrayal, and vicious gossip, she is forced to confront the tragic cruelty just beneath the surface of the Gilded Age. First appearing in Scribner's Magazine as a monthly serial, The House of Mirth was a runaway bestseller upon its release as a full-length novel in 1905. Hailed as "a fireworks display of brilliantly sardonic social satire deepened by a story of thwarted love" by the Wall Street Journal, it was the first popular and critical success for Edith Wharton, who went on to become the first female author to win the Pulitzer Prize. Since its initial publication, The House of Mirth has been adapted into two feature films and continues to captivate modern readers. This ebook has been professionally proofread to ensure accuracy and readability on all devices.